2020
DOI: 10.1017/s0025315420000259
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology and diet of the longtail butterfly rayGymnura poecilura(Shaw, 1804) along western Bay of Bengal

Abstract: The reproductive biology and diet of the longtail butterfly ray Gymnura poecilura is described based on 630 specimens (N = 377 females and 253 males). The mean disc width (WD) of females and males was 576.7 mm (range = 190–920 mm) and 416.3 mm (230–550 mm), respectively. Sexual dimorphism in size was seen, with the maximum size of males being only 60% of the maximum female size. The disc widths at 50% maturity (WD50) were estimated to be 506.5 mm (females) and 435.9 mm (males). The mean uterine fecundity was 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(26 citation statements)
references
References 27 publications
2
24
0
Order By: Relevance
“…In the family Aetobatidae, size and age at sexual maturity were known previously for only male spotted eagle ray A. narinari (ocellated eagle ray A. ocellatus at present) from Australia (DW at 50% sexual maturity of 130.6 cm) (Schluessel et al, 2010). Size and age disparity between sexes has been reported for other stingray species such as the longtail butterfly ray Gymnura poecilura (Menon et al, 2020), whiptail stingray Dasyatis chrysonota (Ebert and Cowley, 2009), and bat ray Myliobatis californica (Martin and Cailliet, 1988b) might be typical of Myliobatiforms and related to their reproductive mode (Martin and Cailliet, 1988b;Capapé, 1993;Furumitsu et al, 2010Furumitsu et al, , 2019. For viviparous species larger females are advantageous, as the increased internal space for developing embryos enables larger young and/or higher fecundity at parturition (Furumitsu et al, 2019).…”
Section: Reproduction and Size At Sexual Maturitymentioning
confidence: 99%
“…In the family Aetobatidae, size and age at sexual maturity were known previously for only male spotted eagle ray A. narinari (ocellated eagle ray A. ocellatus at present) from Australia (DW at 50% sexual maturity of 130.6 cm) (Schluessel et al, 2010). Size and age disparity between sexes has been reported for other stingray species such as the longtail butterfly ray Gymnura poecilura (Menon et al, 2020), whiptail stingray Dasyatis chrysonota (Ebert and Cowley, 2009), and bat ray Myliobatis californica (Martin and Cailliet, 1988b) might be typical of Myliobatiforms and related to their reproductive mode (Martin and Cailliet, 1988b;Capapé, 1993;Furumitsu et al, 2010Furumitsu et al, , 2019. For viviparous species larger females are advantageous, as the increased internal space for developing embryos enables larger young and/or higher fecundity at parturition (Furumitsu et al, 2019).…”
Section: Reproduction and Size At Sexual Maturitymentioning
confidence: 99%
“…Reproductive biology of gymnurids has been studied in varying degrees since the 19th century until recent years. Nonetheless, information on reproduction had been reported only in some Gymnura species, namely, G. poecilura (James, 1966; Muktha et al ., 2020; Raje & Zacharia, 2009), G. zonura (White & Dharmadi, 2007), Gymnura altavela (Alkusairy et al ., 2014; Paiva et al ., 2018; Taylan et al ., 2019), Gymnura marmorata (Maria et al ., 2019), G. micrura (Parsons, 2017; Raje, 2003; Wood‐Mason & Alcock, 1890; Yokota et al ., 2012; Yokota & Lessa, 2007) and Gymnura australis (Jacobsen et al ., 2009). Generally, gymnurids are viviparous, where a yolk sac initially nourishes embryos, then embryos absorb uterine milk rich in proteins and lipids produced by the mother for embryonic development until birth (Conrath, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Generally, gymnurids are viviparous, where a yolk sac initially nourishes embryos, then embryos absorb uterine milk rich in proteins and lipids produced by the mother for embryonic development until birth (Conrath, 2004). Several studies have indicated that the maximum uterine fecundity for most gymnurids is between three and nine (Daiber & Booth, 1960; Jacobsen et al ., 2009; James, 1966; Muktha et al ., 2020; White & Dharmadi, 2007; Wood‐Mason & Alcock, 1890). Furthermore, some gymnurid species, that is, G. poecilura (Muktha et al ., 2020), G. altavela (Alkusairy et al ., 2014; Parsons, 2017), G. micrura (Parsons, 2017), the mazatlan butterfly ray Gymnura crebripunctata, G. marmorata (Smith et al ., 2009) and G. australis (Jacobsen et al ., 2009) exhibit sexual dimorphism in body size where females mature at larger sizes than males.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations